ANALISIS PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP LOYALITAS PELANGGAN YANG DI MEDIASI OLEH KEPUASAN PELANGGAN - Rasyid Hidayat Ramadhan; Ihwan Susila (LP2M Universitas Bina Bangsa, 2024)
The purpose of this study is to analyze the influence of product quality and price on customer loyalty mediated by customer satisfaction. The type of research used in the study uses quantitative methods. The population in this study is customers who have used Telkomsel starter packs at least once in Surakarta City. The sampling technique used in this study is non-probability sampling with the purposive sampling method. The total sample of this study is 150 respondents. This study uses primary data in its preparation. The data collection method used in this study is by distributing online questionnaires. The data analysis technique in this study uses Partial Least (PLS) with SMARTPLS software. The result of this study is that product quality and price have a positive and significant influence on customer satisfaction. Product quality and price have a positive and significant influence on customer loyalty. Customer satisfaction has a positive and significant influence on Customer Loyalty. Product quality has a positive and significant influence on customer loyalty through customer satisfaction. Price has a positive and significant influence on customer loyalty through customer satisfaction